Neurology at the Bedside - Kondziella, Daniel; Waldemar, Gunhild (Springer London : Imprint: Springer, 2014)
This book teaches readers the clinical skills residents in neurology have to acquire in the course of their training, and approaches neurology like a doctor approaches a patient: first there is a chapter on how to perform an efficient neurological history according to neuroanatomical key features, then a chapter on the bedside examination, followed by chapters on differential diagnosis, diagnostic procedures and lastly, the treatment.    Neurology at the Bedside aims to provide readers with a personal clinical mentor. It takes them by the hand and guides them through the whole patient encounter from the history to the treatment, at each step pointing out what is essential and what is not. Extensive differential diagnostic flow charts and detailed treatment suggestions make it a perfect coat pocket reference for the wards. In addition, more than 50 unique case histories cover the entire spectrum of the field.   Neurology at the Bedside is written for neurologists in training: residents as well as senior house officers. Also medical students, general practitioners and others with an interest in neurology will find invaluable information here that is difficult to look up in traditional textbooks or online references.